The role of norms in facilitating productive struggle - Nusser, Tegan William (Kansas State University, 2022)
This study links the teaching practice of productive struggle, a psychological perspective of classroom activities, and the classroom microculture, an interactionist perspective that combines sociocultural and psychological considerations (Cobb & Yackel, 1996). The research question for this study is: In what ways does a teacher negotiate the establishment of classroom norms in order to facilitate productive struggle? To answer this question, this study uses an analytic autoethnographic approach (Anderson, 2006) with analysis and findings preceding and following layered accounts (Ronai, 1995) describing instructional episodes. Reflexive journal entries following days of instruction in addition to lesson plans and curricular materials generated the data for this study. Coding of data revealed connections between the classroom microculture and productive struggle framework (Warshauer, 2015a). This study suggests classroom norms are continually renegotiated over time as teachers and students intersubjectively determine what is acceptable in the classroom—whether norms are “taken as shared” (Yackel, 2001, p. 6). Regarding the classroom microculture, this study suggests that social norms provide supports for how students can collectively engage in struggle, that sociomathematical norms contribute to how students approach engaging in mathematics, and that classroom mathematical practices influence how students engage in struggling with novel mathematics. It further suggests that teachers’ responses to student struggle shape the reestablishment and renegotiation of classroom norms. Implications, limitations, and suggestions for future research are discussed.
Keywords: Productive struggle; Social norms; Sociomathematical norms; Classroom mathematical practices; Analytic autoethnography